SECURE IMAGE STEGANOGRAPHY USING GHM: HIDING TEXT IN PLAIN SIGHT - ABDULLAH , SARAH FAEQ; NAWAF, SHAHIR FLEYEH (Journal of Duhok University, 2023)
Steganography is a method for concealing confidential information in digital images in a way that is imperceptible to humans. However, existing steganographic techniques are frequently vulnerable to assaults such as steganalysis, which can detect the presence of hidden data. The purpose of this work is to develop a method for securely embedding text data within images while minimizing the visual impact on the carrier image. This research paper introduces an efficient method for image steganography by leveraging the GHM GHM(Geronimo-Hardin-Massopust) multiwavelet transform and n-bit Least Significant Bit (LSB) techniques. The proposed algorithm consists of three stages and for six different cases according to the altering of n- bits of the Least Significant Bit (LSB) embedding algorithm. Quality and safety of the stego-images were evaluated by   experimental evaluations using metrics like Peak signal-to-noise ratio(PSNR), Root Mean Square Error (RMSE), and Structural Similarity Index Measure(SSIM). The results consistently demonstrated advantages of the suggested algorithm in terms of Peak signal-to-noise ratio(PSNR) about 24% improvement over the Least Significant Bit (LSB) techniques and 17% improvement over the the DWT (Discrete Wavelet Transform),also in terms of the Root Mean Square Error (RMSE), about 78% improvement over the Least Significant Bit (LSB) techniques and 67% improvement over the the DWT (Discrete Wavelet Transform) in average. The proposed approach significantly enhanced image quality while maintaining a high level of resemblance to the original image, showcasing its efficacy in preserving the underlying structure of the cover image.